(untitled) (Research, Society and Development, 2022)
Objective: identify the evolution of childhood vaccination coverage in Brazil between 2010 and 2020 and the impacts on immunization goals caused by the COVID-19 pandemic. Method: an ecological observational study, with data on vaccination coverage in children under one year of age, in Brazil, between 2010 and 2020. These data were collected through the Sistema de Informações do Programa Nacional de Imunizações, while the demographic data were collected through the Sistema de Nascidos Vivos, socioeconomic conditions by the Instituto Brasileiro de Geografia e Estatística and social isolation through the company Inloco. They were analyzed statistically by simple linear regression and linear correlation. Results: the sample estimated at 31,844,835 children showed a reduction in coverage for BCG (Coefficient=-2.718; p<0.001) and Triple Viral (Coefficient=-2.200; p=0.014), an increase for Yellow Fever (Coefficient=1.264; p =0.032) and Pentavalent (Coefficient=7.418; p=0.031), and stability for Rotavirus (Coefficient=-0.445; p=0.401). In 2020, there was no correlation between levels of social isolation and drops in coverage, only in the North region, this relationship, for Triple Viral (Spearman Correlation=-0.683; p=0.020), proved to be significant. Conclusion: profile of low vaccination coverage between 2010 and 2020 due to factors such as socioeconomic status and vaccine hesitancy. Still, there was stability in 2020, as social isolation was not associated with low coverage, which had already been falling before the pandemic.